2013
DOI: 10.1590/s0104-66322013000300016
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and gas permeation study of PSf/MgO nanocomposite membrane

Abstract: -Nanocomposite membranes composed of polymer and inorganic nanoparticles are a novel method to enhance gas separation performance. In this study, membranes were fabricated from polysulfone (PSf) containing magnesium oxide (MgO) nanoparticles and gas permeation properties of the resulting membranes were investigated. Membranes were prepared by solution blending and phase inversion methods. Morphology of the membranes, void formations, MgO distribution and aggregates were observed by SEM analysis. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Membrane technology plays an important role in various environmental and energy processes, such as CO 2 capture (Zou and Ho, 2008;Hussain and Hägg, 2010;Brunetti et al, 2010;Yang et al, 2008), biogas upgrading (Deng and Hägg, 2010;Makaruk et al, 2010;Pakizeh et al, 2013;Momeni and Pakizeh, 2013), natural gas sweetening (Bernardo et al, 2009;Peters et al, 2011;Baker and Lokhandwala, 2008), and hydrogen production (Sà et al, 2009;Clem et al, 2006) and can potentially compete with some traditional separation methods in terms of energy requirements and economic costs (Xuezhong and Hägg, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane technology plays an important role in various environmental and energy processes, such as CO 2 capture (Zou and Ho, 2008;Hussain and Hägg, 2010;Brunetti et al, 2010;Yang et al, 2008), biogas upgrading (Deng and Hägg, 2010;Makaruk et al, 2010;Pakizeh et al, 2013;Momeni and Pakizeh, 2013), natural gas sweetening (Bernardo et al, 2009;Peters et al, 2011;Baker and Lokhandwala, 2008), and hydrogen production (Sà et al, 2009;Clem et al, 2006) and can potentially compete with some traditional separation methods in terms of energy requirements and economic costs (Xuezhong and Hägg, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…T g value for pure PSF is in accordance with the literature reported T g of pure PSF. 30 DSC results for a composite membrane with coating time of 10 min also exhibited single T g at 174.13 8C. This indicates the complete phase transition between PDMS and PSF, stating that PDMS and PSF were homogeneously crosslinked together in composite membrane.…”
mentioning
confidence: 73%
“…If a polymer has a higher affinity to filler, it will demonstrate reduced mobility and reduced free volume and a higher T g . Momeni and Pakizeh have shown that increase in MgO nanoparticles loading in PSU matrix increased the T g of PSU.…”
Section: Resultsmentioning
confidence: 99%